2023
DOI: 10.1681/asn.0000000000000164
|View full text |Cite
|
Sign up to set email alerts
|

Dnajb11-Kidney Disease Develops from Reduced Polycystin-1 Dosage but not Unfolded Protein Response in Mice

Sounak Ghosh Roy,
Zhigui Li,
Zi Guo
et al.

Abstract: Background: Patients with heterozygous inactivating mutations in DNAJB11 manifest with cystic but not enlarged kidneys and renal failure in adulthood. Pathogenesis is proposed to resemble an overlap of autosomal dominant polycystic kidney disease (ADPKD) and autosomal dominant tubulointerstitial kidney disease (ADTKD), but this phenotype has never been modeled in vivo. DNAJB11 encodes an Hsp40 co-chaperone in the endoplasmic reticulum (ER): the site of maturation of the ADPKD polycystin-1 (PC1) pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 56 publications
2
5
0
Order By: Relevance
“…does not result in cystic kidneys suggests that cysts are not derived from distal tubular segments where Ksp-Cre is expressed (thick ascending loop of Henle, distal tubule, and collecting duct). A recent study also reported the absence of cysts in Ksp-Cre; Dnajb11 fl/fl mice (42). It was shown in this study that a reduction in Pkd1 copy number (Pkd1 +/-) in these animals resulted in cyst formation (42).…”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations
“…does not result in cystic kidneys suggests that cysts are not derived from distal tubular segments where Ksp-Cre is expressed (thick ascending loop of Henle, distal tubule, and collecting duct). A recent study also reported the absence of cysts in Ksp-Cre; Dnajb11 fl/fl mice (42). It was shown in this study that a reduction in Pkd1 copy number (Pkd1 +/-) in these animals resulted in cyst formation (42).…”
Section: Discussionsupporting
confidence: 62%
“…A recent study also reported the absence of cysts in Ksp-Cre; Dnajb11 fl/fl mice (42). It was shown in this study that a reduction in Pkd1 copy number (Pkd1 +/-) in these animals resulted in cyst formation (42). Since patients with ADPKD caused by monoallelic DNAJB11 mutations do not have heterozygous PKD1 mutations it was speculated that a lower basal PC1 dosage in humans compared to mice may explain cyst formation in the human disease (42).…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…Notably, we found that ATF4 is upregulated in all PKD models described above, including KspCre;Pkd1 ΔC/flox kidneys at P4 ( Fig 3B ) and P45-tamoxifen-induced Tam-Cre;Pkd1 ΔC/flox kidneys at P160 ( Fig 3C ). Of interest, the ATF4-ASNS axis is known to be activated in response to ER stress by PERK-dependent activation of unfolded protein response (UPR), a pathway that has been shown not to be de-regulated in PKD (Fedeles et al , 2015; Roy et al , 2023), but also during an imbalance in amino acids availability in cells and tissues via activation of the General Control Nonderepressible-2- kinase (GCN2) within the so called amino acid response (AAR) that converges downstream with the PERK pathway on eIF2alpha which translationally regulates ATF4 levels (Lomelino et al , 2017) ( Fig 3A ). This process is mimicked by the limitation of essential amino acids (EAAs) in cell culture (Jin et al , 2021), whereby GCN2 acts as a metabolic sensor for the depletion of amino acids, via the binding of uncharged tRNAs (Kanno et al , 2020).…”
Section: Resultsmentioning
confidence: 99%